RuS2 / CoNi2S4@NF high-efficiency electrocatalyst, preparation method thereof and application in electrocatalytic oxygen evolution
The synthesis of RuS2/CoNi2S4@NF electrocatalysts by two-step hydrothermal method solved the problems of slow hydrodynamics of neutral electrolysis and high cost of precious metal catalysts, and achieved the effect of efficient preparation of oxygen under alkaline conditions, with excellent electrochemical performance and stability.
Patent Information
- Application Number
- CN202211323585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-10-27
AI Technical Summary
In the prior art, the kinetics of neutral electrolytic water are slow, the scarcity and high cost of precious metal platinum group metal catalysts limit their widespread application, and the stability and OER activity of CoNi2S4 do not meet the standards and cannot be used in industrial applications.
RuS2/CoNi2S4@NF high-efficiency electrocatalyst was synthesized by a two-step hydrothermal method, using blank nickel foam as the substrate, first synthesize the CoNi2S4 precursor, and then loading RuS2 to prepare an electrocatalyst with a tightly packed nanosphere morphology.
It realizes efficient preparation of oxygen in electrolyzed water under KOH alkaline conditions, has excellent electrochemical catalytic activity and stability, and has low overpotential, which is suitable for industrial applications.
Smart Images

Figure HDA0003911524830000011 
Figure HDA0003911524830000012 
Figure HDA0003911524830000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalyst preparation and application, and specifically relates to a method for preparing a RuS2 / CoNi2S4@NF high-efficiency electrocatalyst and its application in oxygen evolution in electrocatalytic water decomposition. Background Art
[0002] Water electrolysis can be performed in alkaline, neutral and acidic media. Neutral water electrolysis is environmentally friendly and suitable for electrolysis of microorganisms, but due to the low concentration of reactants adsorbed on the catalyst surface and the large energy loss during the water electrolysis process, water electrolysis in neutral media has the problem of slow kinetics. In contrast, alkaline water electrolysis is more widely used due to its low cost and good catalyst stability.
[0003] At present, precious metal platinum group metal catalysts are the most effective catalysts for water electrolysis, but their scarcity and high cost greatly limit their widespread practical commercial application. In recent years, a considerable number of precious metal-free materials have emerged for water electrolysis, such as transition metal sulfides, oxides, selenides, nitrides, phosphides, carbon-based materials and their compounds. Among them, the cost of Ru is less than 25% of that of metal Pt, and Ru-based materials have been applied in various catalytic fields, such as electrocatalysis, photocatalysis, hydrodesulfurization and supercapacitors. Ru-based catalysts have excellent electrocatalytic activity due to their rich redox chemistry and multivalent states. RuS2 is one of the typical Ru-based materials, which is usually used as an efficient catalyst in hydrodesulfurization. RuS2 exhibits excellent HER activity due to its good hydrogen binding ability. In addition, Ru, as a more oxygen-philic element, has a stronger water dissociation ability than Pt, while RuS2 is less used in electrocatalytic oxygen evolution, and the oxygen evolution performance of RuS2 alone is poor. In addition, bimetallic nickel-cobalt sulfides, such as CoNi2S4, have shown remarkable conductivity, unique bimetallic track structure and electrochemical performance due to their superior conductivity compared to simple metal sulfides. However, the stability and OER activity of CoNi2S4 are still not up to standard. The reasons include electrolyte corrosion, low active site density, poor contact between materials and electrodes, and many other reasons, which make it unsuitable for industrial applications. Summary of the invention
[0004] The purpose of the present invention is to provide a RuS2 / CoNi2S4@NF high-efficiency electrocatalyst and a preparation method thereof, which is applied to the electrolysis of water to produce oxygen under KOH alkaline conditions and has excellent electrochemical catalytic activity and stability.
[0005] The technical solution of the present invention:
[0006] The preparation method of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst provided by the present invention is:
[0007] The present invention first places blank nickel foam in an organic solvent and a dilute acid solution for ultrasonic cleaning in sequence, then synthesizes a CoNi2S4 precursor on a treated nickel foam (NF) substrate using a hydrothermal method with a cobalt source, a nickel source and a sulfur source, and then loads RuS2 on the CoNi2S4@NF precursor using a hydrothermal method to finally obtain a RuS2 / CoNi2S4@NF electrocatalyst.
[0008] The specific process is:
[0009] (1) The nickel foam (NF) was sequentially immersed in 3 mol / L hydrochloric acid solution, acetone solution, ethanol and ultrapure water, and ultrasonically cleaned for 15 min each time. After being cleaned, the nickel foam was taken out and dried overnight.
[0010] (2) Dissolve Co(NO3)2·6H2O as a cobalt source and Ni(NO3)2·6H2O as a nickel source in ethylene glycol and stir to mix them evenly; then add thiourea as a sulfur source and stir to mix them evenly; transfer the solution and the nickel foam treated in step (1) to a polytetrafluoroethylene-lined autoclave and place them in a 160°C forced air drying oven for hydrothermal reaction for 16 hours. After the reaction is completed, take out the product and wash it with deionized water and ethanol in turn, and finally place it in a vacuum drying oven to dry to obtain CoNi2S4@NF. The mass ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 1:2. The mass ratio of thiourea to the area of nickel foam is 0.45:1g / cm 2 .
[0011] (3) RuCl3 and L-cysteine were dissolved in an aqueous solution of ethylene glycol, and the mixture was uniformly mixed by ultrasonication and stirring; the solution and the CoNi2S4@NF obtained in step (2) were then transferred to a polytetrafluoroethylene-lined autoclave, and placed in a 160°C forced air drying oven for hydrothermal reaction for 9 hours. After the reaction was completed, the product was taken out and washed with deionized water and ethanol in turn, and finally placed in a vacuum drying oven for drying to obtain the final product, RuS2 / CoNi2S4@NF electrocatalyst. The mass ratio of RuCl3 to L-cysteine was 1:2.3. The volume ratio of ethylene glycol to water in the aqueous solution of ethylene glycol was 1:3.
[0012] Choosing ethylene glycol as solvent can better composite materials. However, using water or ethanol as solvent cannot successfully synthesize RuS2 and composite.
[0013] RuS2 / CoNi2S4@NF electrocatalyst RuS2 accounts for 5% to 15% by mass in RuS2 / CoNi2S4@NF, preferably 10%.
[0014] The present invention selects appropriate cobalt source, nickel source and sulfur source, controls the temperature of the blast drying oven to synthesize the CoNi2S4@NF precursor on the nickel foam; then controls the mass ratio of RuCl3 and L-cysteine to CoNi2S4@NF, and finally prepares the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst.
[0015] The present invention also provides an application of RuS2 / CoNi2S4@NF high-efficiency electrocatalyst as a working electrode for electrolyzing water to prepare oxygen under KOH alkaline conditions.
[0016] RuS2 / CoNi2S4@NF high-efficiency electrocatalyst is used for electrochemical catalytic oxygen evolution performance. Its performance test method is to use a three-electrode system. The working electrode is an electrode loaded with RuS2 / CoNi2S4@NF high-efficiency electrocatalyst, the counter electrode is a graphite rod electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is 1 mol / L KOH solution.
[0017] The technical effects achieved by the present invention are:
[0018] (1) The catalyst provided by the present invention is a RuS2 / CoNi2S4@NF high-efficiency electrocatalyst synthesized by a two-step hydrothermal composite material, and its synthesis process is green and simple, has good repeatability, and has wide applicability;
[0019] (2) The RuS2 / CoNi2S4@NF high-efficiency electrocatalyst provided by the present invention obtains a high-efficiency electrocatalyst with a tightly packed nano-spherical morphology by controlling the hydrothermal temperature and the mass ratio of the composite, thereby increasing the electrochemical activity of the electrocatalytic oxygen evolution reaction;
[0020] (3) The RuS2 / CoNi2S4@NF electrocatalyst provided by the present invention was used to electrolyze water in an alkaline electrolyte with a concentration of 1 mol / L KOH to produce oxygen. The RuS2 / CoNi2S4@NF electrocatalyst was used as the working electrode at a current density of 10 mA / cm 2 The overpotential of oxygen evolution is only 152 mV, showing excellent electrochemical performance and stability for the oxygen evolution reaction in water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD diagrams of RuS2 / CoNi2S4@NF obtained in Example 1 of the present invention and NF and CoNi2S4@NF obtained in Comparative Examples 1-2.
[0022] Figure 2 This is the SEM image of 10% RuS2 / CoNi2S4@NF obtained in Example 1 of the present invention.
[0023] Figure 3LSV polarization curves of 10% RuS2 / CoNi2S4@NF, RuS2 / CoNi2S4@NF (220°C) and NF, CoNi2S4@NF (160°C), and CoNi2S4@NF (220°C) obtained in Example 1, Example 4 and Comparative Examples 1-3 of the present invention, electrolyzing water for oxygen evolution in an alkaline solution of 1.0 mol / L KOH.
[0024] Figure 4 LSV polarization curves of 10% RuS2 / CoNi2S4@NF, 5% RuS2 / CoNi2S4@NF, 15% RuS2 / CoNi2S4@NF and NF, CoNi2S4@NF (160°C), and RuS2@NF obtained in Examples 1-3 of the present invention and Comparative Examples 1-2 and Comparative Example 4 for electrolysis of water and oxygen evolution in an alkaline solution of 1 mol / L KOH.
[0025] Figure 5 This is the LSV polarization curve of the 10% RuS2 / CoNi2S4@NF obtained in Example 1 of the present invention before and after 1000CV cycles.
[0026] Figure 6 The 10%RuS2 / CoNi2S4@NF obtained in Example 1 of the present invention is 10mA / cm 2 Chronopotentiographs at different current densities. DETAILED DESCRIPTION
[0027] The technical features of the present invention are further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited thereto.
[0028] Example 1
[0029] 1. Preparation of NF
[0030] The nickel foam (NF) (1 cm×1 cm) was immersed in 3 mol / L hydrochloric acid solution, acetone solution, ethanol and ultrapure water in turn, and ultrasonically cleaned for 15 min each. After cleaning, the nickel foam was taken out and finally dried in a vacuum drying oven at 60°C overnight.
[0031] 2. Preparation of CoNi2S4@NF
[0032] 0.25 g Co(NO3)2·6H2O and 0.5 g Ni(NO3)2·6H2O were weighed, dissolved in 40 mL ethylene glycol, and stirred for 10 min to mix evenly; then 0.45 g thiourea was added and stirred for 30 min to mix evenly; the solution and the nickel foam treated in step (1) were transferred to a polytetrafluoroethylene-lined autoclave, and then placed in a 160° C. forced air drying oven for hydrothermal reaction for 16 h. After the reaction was completed, the product was taken out and washed with deionized water and ethanol in turn, and finally dried in a 60° C. vacuum drying oven to obtain CoNi2S4@NF.
[0033] 3. Preparation of RuS2 / CoNi2S4@NF
[0034] 31.5 mg RuCl3 and 73.5 mg L-cysteine were weighed and dissolved in 60 mL of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to water was 1:3), and the mixture was ultrasonically mixed and stirred to make it uniform. The solution and the CoNi2S4@NF obtained in step (2) were then transferred to a polytetrafluoroethylene-lined autoclave and placed in a 160°C forced air drying oven for hydrothermal reaction for 9 h. After the reaction was completed, the product was taken out and washed with deionized water and ethanol in turn, and finally dried in a 60°C vacuum drying oven to obtain the final product, 10% RuS2 / CoNi2S4@NF, a highly efficient electrocatalyst.
[0035] The XRD pattern of 10%RuS2 / CoNi2S4@NF prepared in Example 1 is as follows Figure 1 As shown, SEM pictures are Figure 2 As shown in the figure, the LSV polarization curves before and after 1000CV cycle are as follows Figure 5 As shown in the chronopotentiograph, Figure 6 As shown. From the XRD and scanning electron microscopy images, it can be seen that the XRD characteristic peaks of the finally prepared 10%RuS2 / CoNi2S4@NF electrocatalyst are obvious. The SEM morphology is a densely packed nanosphere. From the LSV polarization curve before and after 1000CV cycles, it can be seen that the LSV graph before and after 1000CV cycles shows negligible degradation under the same conditions, indicating that the finally prepared 10%RuS2 / CoNi2S4@NF electrocatalyst has excellent stability. From the chronopotentiograph, it can be seen that at 10mA / cm 2 After 16 h of durability testing at a constant current density, the overpotential of the 10%RuS2 / CoNi2S4@NF electrocatalyst only decreased slightly, indicating its excellent long-term stability for oxygen evolution electrocatalysis in alkaline solution of KOH.
[0036] application
[0037] 1. Activation treatment of electrocatalyst
[0038] (1) A three-electrode system was used, the working electrode was the electrode of the 10% RuS2 / CoNi2S4@NF electrocatalyst in Example 1, the counter electrode was a graphite rod electrode, the reference electrode was a Hg / HgO electrode, and the electrolyte was a 1 mol / L KOH solution.
[0039] (2) Cyclic voltammetry (CV) activation: Shanghai Chenhua DH7000 electrochemical workstation was used, and the cyclic voltammetry program was adopted. The test range was 0-0.8V vs. RHE, the scan rate was 50mV / s, and the number of cycles was 20. After the program was completed, the 10%RuS2 / CoNi2S4@NF electrocatalyst electrode reached a stable state.
[0040] 2. Linear sweep voltammetry (LSV) test
[0041] After activation by cyclic voltammetry, the electrochemical workstation program was switched to linear sweep voltammetry program with a test interval of 0-0.8 V vs. RHE and a scan rate of 5 mV / s. The electrocatalyst was activated at a current density of 10 mA / cm in an alkaline electrolyte of 1 mol / L KOH. 2 When the overpotential of oxygen evolution is 152mV, Figure 3 shown.
[0042] Example 2
[0043] Compared with Example 1, the difference is: Preparation of RuS2 / CoNi2S4@NF. Weigh 16.42 mg of RuCl3 and 36.75 mg of L-cysteine, dissolve in 60 mL of ethylene glycol aqueous solution (the volume ratio of ethylene glycol to water is 1:3), and mix them evenly by ultrasonication and stirring. Other preparation methods are the same as in Example 1.
[0044] The application method is the same as that of Example 1. The 5% RuS2 / CoNi2S4@NF electrocatalyst prepared in Example 2 was used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , the overpotential of oxygen evolution is 212mV.
[0045] Example 3
[0046] Compared with Example 1, the difference is: Preparation of RuS2 / CoNi2S4@NF. Weigh 49.26 mg of RuCl3 and 113.2 mg of L-cysteine, dissolve in 60 mL of ethylene glycol aqueous solution (the volume ratio of ethylene glycol to water is 1:3), and mix them evenly by ultrasonication and stirring. Other preparation methods are the same as in Example 1.
[0047] The application method is the same as that of Example 1. The 15% RuS2 / CoNi2S4@NF electrocatalyst prepared in Example 3 was used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , the overpotential of oxygen evolution is 280mV.
[0048] Example 4
[0049] Compared with Example 1, the differences are as follows: Preparation of CoNi2S4@NF. The temperature of the blast drying oven is set to 220°C. Other preparation methods are the same as in Example 1.
[0050] The application method is the same as that of Example 1. The RuS2 / CoNi2S4@NF (220°C) electrocatalyst prepared in Example 4 was used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When the temperature is lower than 160℃, the overpotential of oxygen evolution is 272mV. The temperature will affect the crystallinity, defects and conductivity of the synthesized CoNi2S4@NF. When the temperature is lower than 160℃, the synthesized CoNi2S4@NF has poor crystallinity and conductivity, and the catalyst effect will deteriorate.
[0051] Comparative Example 1
[0052] Compared with Example 1, the difference is that: Steps 2 and 3 are not included, and only the foamed nickel (NF) pretreated in Step 1 is used.
[0053] The application method is the same as that of Example 1. The NF electrocatalyst prepared in Example 1 is used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , its overpotential for oxygen evolution is 601mV, and its oxygen evolution performance is very poor.
[0054] Comparative Example 2
[0055] Compared with Example 1, the difference is that there is no step 3. The other preparation methods are the same as in Example 1.
[0056] The application method is the same as that of Example 1. The CoNi2S4@NF (160°C) electrocatalyst prepared in Example 2 is used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , the overpotential of oxygen evolution is 327mV.
[0057] Comparative Example 3
[0058] Compared with Example 1, the difference is that: there is no step 3, and the temperature of the blast drying oven in step 2 is set to 220° C. Other preparation methods are the same as in Example 1.
[0059] The application method is the same as that of Example 1. The CoNi2S4@NF (220°C) electrocatalyst prepared in Example 3 is used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , its oxygen evolution overpotential is 369mV.
[0060] Comparative Example 4
[0061] Compared with Example 1, the difference is that: there is no step 2, and there is no step 3 of transferring the CoNi2S4@NF obtained in step (2) to the polytetrafluoroethylene-lined autoclave. The other preparation methods are the same as in Example 1.
[0062] The application method is the same as that of Example 1. The RuS2@NF electrocatalyst prepared in Example 4 is used to electrocatalyze water decomposition to produce oxygen in an alkaline electrolyte with a concentration of 1 mol / L KOH. 2 When , its oxygen evolution overpotential is 340mV.
[0063] The specific implementation methods described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above is only the most preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An application of RuS2 / CoNi2S4@NF electrocatalyst, characterized in that: RuS2 / CoNi2S4@NF electrocatalyst is used for electrocatalytic oxygen evolution from water under alkaline conditions; The specific steps of the preparation method of RuS2 / CoNi2S4@NF electrocatalyst are as follows: (1) Dissolve Co(NO3)2·6H2O as a cobalt source and Ni(NO3)2·6H2O as a nickel source in ethylene glycol and stir to mix them evenly; then add thiourea as a sulfur source and stir to mix them evenly; transfer the solution and the cleaned nickel foam to an autoclave for a hydrothermal reaction; after the reaction is completed, take out the product, wash it, and dry it to obtain CoNi2S4@NF; (2) RuCl3 and L-cysteine are dissolved in an aqueous solution of ethylene glycol, the mass ratio of RuCl3 to L-cysteine being 1:2.3, and the mixture is uniformly mixed by ultrasonication and stirring; the solution and the CoNi2S4@NF obtained in step (1) are then transferred to an autoclave for a hydrothermal reaction, and the product is taken out after the reaction is completed, washed, and dried to obtain the product RuS2 / CoNi2S4@NF high-efficiency electrocatalyst.
2. The use of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst according to claim 1, characterized in that: In step (1), the mass ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 1:
2.
3. The use of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst according to claim 1, characterized in that: The ratio of the mass of thiourea to the area of nickel foam in step (1) is 0.45:1 g / cm 2 .
4. The use of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is set to 160° C. and the heating time is set to 16 h.
5. The use of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst according to claim 1, characterized in that: In step (2), the volume ratio of ethylene glycol to water in the aqueous solution of ethylene glycol is 1:
3.
6. The use of the RuS2 / CoNi2S4@NF high-efficiency electrocatalyst according to claim 1, characterized in that: The hydrothermal reaction temperature of step (2) was set to 160° C., and the hydrothermal reaction time was set to 9 h.
Citation Information
Patent Citations
Cobalt-nickel metal sulfide bifunctional electrocatalyst as well as preparation method and application thereof
CN115029709A
Unsupported and supported promoted ruthenium sulfide catalyst with high catalytic activity for hydrocarbon hydrotreatments and its method
US20130157842A1